Aktivitas Antibakteri Ekstrak Etanol Daun Sukun (Artocarpus altilis) Terhadap Bakteri Staphylococcus aureus Dan Escherichia coli - Fiana, Fuan Maharani; Kiromah, Naelaz Zukhruf Wakhidatul; Purwanti, Ery (Pharmacon: Jurnal Farmasi Indonesia)
Diarrhea is caused by bacterial infections, especially Staphylococcus aureus and Escherichia coli. The breadfruit leaves (Artocarpus altilis) are known contain flavonoid compounds, alkaloids, saponins, and tannins which can be used as antibacterial. This research was conducted to determine the ethanol extract of the breadfruit leaves against Staphylococcus aureus and Escherichia coli bacteria. The manufacture of the breadfruit leaf extract was using a maceration method with 96% ethanol solvent. The result of the tube test and the TLC test was positive, the breadfruit leaf extract containing flavonoids and tannins which have potential as antibacterial. The antibacterial test was carried out using the disc diffusion method (Kirby-Bauer test) against Staphylococcus aureus and Escherichia coli bacteria incubated for 1 x 24 hours. The extract concentrations tested were 10%, 15% and 20%. The positive control was using erythromycin antibiotics and the negative control was using aquades. The identification of the chemical content of plants is done by tube test and the TLC test. The results of incubation of the breadfruit leaf extract with concentrations of 10%, 15% and 20% against Staphylococcus aureus bacteria, the average diameter of inhibitory zones respectively were 3.67, 3.50 and 2.67 mm with the positive control diameter of inhibition zone was 18.5 mm, the negative control diameter of inhibition zone was 0 mm. The results of incubation of the breadfruit leaf extract with concentrations of 10%, 15% and 20% against Escherichia coli bacteria, the average diameter of inhibitory zones respectively were 5.33, 3.17 and 3.33 mm with the positive control inhibition zone diameter of 28.5 mm and the negative control of inhibition zone diameter of 0 mm. The activity of ethanol extract of the breadfruit leaves against the Staphylococcus aureus and Escherichia coli bacteria is included in the weak category.